Analisis Hasil Belajar Mahasiswa Pada Materi Regresi Linier Berdasarkan Tingkat Adversity Quotient - Anita Sari (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
This study aims to describe student achievement in linear regression material in terms of students' ability to think, organize, manage and face challenges or Adversity Quotient (AQ). The subjects in this study were a class of 21 students of the Animal Husbandry Agribusiness Study Program. The research method used in this research is descriptive qualitative. The instruments used in this study were a matter of description of the linear regression material and the Adversity Quotient questionnaire. The results showed that students were classified into 3 types of Adversity Quotient, namely climbers, campers, and quitters in the following learning outcomes: students who scored at intervals of 20-52 only had two categories of students, namely quitters and campers. While at the score interval of 53-68 there are also two categories of students, namely Climbers and Campers. The score interval 69-84 is an interval that has various types of AQ, there are categories of Campers, Climbers and Quitters students. Whereas for the score interval of 85-100 there are only Climbers students. Based on the acquisition of AQ scores obtained by students, it can be stated that the level of AQ owned by students is directly proportional to the learning outcomes obtained. So that in this study the Adversity Quotient has a positive impact on optimizing the achievement of learning outcomes.